IMPLEMENTATION OF ARABIC LEARNING AT MTS NDM (NAHDHATUL MU'ALIMIN) SURAKARTA IN IMPROVING LEARNING OUTCOMES - Mustofa, M (Proceeding of International Conference of Islamic Education, 2023)
Arabic language learning is important for every Muslim because it is the language of the Quran, Hadith, and the language used by scholars to compile disciplines in Islamic studies. Therefore, in this research, the researcher attempts to investigate the methodology of Arabic language learning at Madrasah Nahdhatul Mualimin Surakarta. As known, there are three types of research methodologies: classical, modern, and mixed. This research utilizes a qualitative method. The findings of this study reveal that the methodology of Arabic language learning in the research subject is a mixed approach.